Why space matters for collaborative innovation networks: on designing enabling spaces for collaborative knowledge creation. (1st January 2014) - Peschl, Markus F.; Fundneider, Thomas
As opposed to managing or controlling innovation processes, this paper proposes the notion of enabling as a more suitable approach to innovation. As a consequence, the concept of enabling spaces is introduced as a space that is designed in such a way that it enables and facilitates processes of collaborative knowledge creation and innovation. In that context, a rather broad notion of space is applied: it goes far beyond architectural/physical space by integrating social, cognitive, emotional, organisational, and epistemological dimensions in an interdisciplinary manner. Both the theoretical background and the methodological approach and design process will be presented. Furthermore, we will discuss a case for an enabling space which functions as a collaborative innovation network. It will turn out that enabling spaces and collaborative innovation networks (COINs) share a lot of characteristics, attitudes, and values.